Exploring the Effectiveness of Automatic Braking System (ABS) (International Journal of Food and Nutritional Sciences, 2022)
A protective anti-skid brake program called as an automatic braking system (ABS) is utilized on busses, trucks, automobiles, and motorbikes as well as on aeroplanes. In order to retain thrust touch with the roadway pavement and provide the driver better command over the car, ABS works by stopping the tyres from locked up when stopping. It is an automatic technique that contains the same cadence and thresholds stopping techniques used by skilled drivers in older braking systems. Because of its quicker reaction time, the steering is simple for the driver. ABS often provides more sophisticated control of the vehicle and reduces halting distances. The purpose of the article is to examine and assess the Antilock Braking System Principles, ABS Applications and Significance, Antilock Braking System Types, ABS Subsystems, and ABS Control Systems. Fuzzy control mechanisms, which have various advantages including resilience, rule-based algorithms, and the universal approximation theorem, may be employed in ABS management to simulate the qualitative components of human understanding.